Buprenorphine MAT as an Imperfect Fix. Issue 2 (June 2018) - Mund, Brian; Stith, Kate
Expanding buprenorphine access in the United States requires evidence-based decision-making that considers both the drug's potential dangers and its potential benefits. Risks associated with buprenorphine misuse and diversion highlight the need for careful, ongoing evaluation during each stage of increased access.